The other side of the coin: an analysis of financial and economic crime (Publications Office of the European Union, 2023)
Serious and organised crime continues to threaten the internal security of the EU. The criminal landscape constantly evolves, as criminals seek out new opportunities and exploit crises for their own interests. Criminal actors involved in economic and financial crimes are highly adept at taking advantage of our economy for their purposes, and at targeting increasing numbers of victims. They capitalise on vulnerabilities in society's systems to generate billions in illicit profits, while applying various strategies, often cyber-enabled, to remain undetected and secure their earnings. Financial crimes, and in particular money laundering, undermine our society not only by infiltrating the legal economy, but also by fostering the growth of a parallel underground society made of individuals who increasingly rely on organised crime for their economic sustenance and livelihood. Vulnerable demographics, and especially vulnerable youngsters who are lacking trust in societal institutions and confidence in the rule of law, are the perfect target pool for such parallel underground society. Due to their intrusive nature, financial and economic crimes are among the most challenging criminal activities to investigate and tackle. A fragmented landscape sees different criminal actors interact with one another, making criminal operations more complex and tangled. Key players typically remain anonymous and operate independently from established criminal structures, often from criminal safe havens. Meanwhile, their techniques and tools advance rapidly. Some recent investigations, including those exploring encrypted communications among criminals, gave unprecedented insight into the system that sustains the finances of organised crime. While law enforcement is untangling the complexity of this underground financial ecosystem, information sharing, investigative focus on key criminal actors, development of technical knowledge and expertise, and public-private partnerships are essential tools for winning the fight against financial and economic crimes.